FIGURATIVE LANGUAGE IN SELENA GOMEZ’ SELECTED SONGS - Ariningsih, Ida Ayu Made Dwi; Jayantini, I.G.A. Sri Rwa; Suastini, Ni Wayan (ID Solutions, 2023)
This article was created with the aim of exploring the use of the figurative language in selected songs from Selena Gomez's album Rare and their meaning. There were three songs chosen, namely Cut You Off, Vulnerable, and A Sweeter Place. This study has two problems formulated in this research, namely: what kind of figurative language is found in Selena Gomez's album entitled Rare and what is the meaning of figurative language found in Selena Gomez's album entitled Rare. The theory to describe figurative language is from Abrams' theory (1999) while the meaning is from Leech's theory (1981). The author found three types of eight types of figurative language, namely 1 simile, 3 hyperbole, and 1 metaphor and found one type of meaning according to Leech (1981), namely connotative meaning